Principal Component Analysis of Oxford Cognitive Screen in Patients With Stroke - Iosa, Marco; Demeyere, Nele; Abbruzzese, Laura; Zoccolotti, Pierluigi; Mancuso, Mauro (Frontiers in Neurology, 2022)
Cognitive deficits occur in most stroke patients and are important predictors of adverse long-term outcome. Early identification is fundamental to plan the most appropriate care, including rehabilitation and discharge decisions. The Oxford Cognitive Screen (OCS) is a simple, valid and reliable tool for the assessment of cognitive deficits in patients with stroke. It contains 10 sub-tests, providing 14 scores referring to 5 theoretically derived cognitive domains: attention, language, number, praxis and memory. However, an empirical verification of the domain composition of the OCS sub-tests in stroke data is still lacking in the literature. A principal component analysis (PCA) was performed on 1973 patients with stroke and 498 healthy participants who were enrolled in OCS studies in the UK and Italy. Six main components were identified relating to the domains of: language and arithmetic, memory, visuomotor ability, orientation, spatial exploration, and executive functions. The comparison between patients and healthy participants, as that between patients with left and right hemisphere damage confirmed the results obtained by the principal component analysis. A clarification about the contribution of each score to the theoretical original domains and to the components identified by the PCA is provided with the aim to foster the usability of OCS for both clinicians and researchers.